2021
DOI: 10.1111/jfpe.13782
|View full text |Cite
|
Sign up to set email alerts
|

Find the centroid: A vision‐based approach for optimal object grasping

Abstract: Recently, the booming development of deep learning techniques facilitates remarkable progress in a wide range of applications, has provided insightful cues in today's modern industry and research societies. For instance, the manufacturing and agricultural industries have witnessed the unparallel dominance in AI vision to integrate the production management. Therefore, owing to its impressive learning capability, this article aims to develop an automated system that can integrate data processing and packaging o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Various studies have demonstrated the effectiveness of object detection techniques, including YOLO and Faster R-CNN, in tackling challenges across food processing and agriculture sectors. These techniques have been applied to various food items, such as carrots, ham, apples, mutton, fruits, shrimp, Nile tilapia, and Atlantic salmon [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated the effectiveness of object detection techniques, including YOLO and Faster R-CNN, in tackling challenges across food processing and agriculture sectors. These techniques have been applied to various food items, such as carrots, ham, apples, mutton, fruits, shrimp, Nile tilapia, and Atlantic salmon [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%